Peningkatan Hasil Pendidikan Nilai - Nilai Kehidupan Sosial melalui Penerapan Pembelajaran Kooperatif - Isminiati, Ch (Dinamika Pendidikan, 2008)
Being able to contribute  in constructive  way to activities of social and democratic society is an essential skill in school and in life. Most of what the child will do in life will be in cooperation  with other people. A consequently, the social skills and social living values in education  are very important to learn. Therefore, teacher needs to choose an appropriate  .instructional  strategies to teach the skills andliving values, i.e.: cooperation, caring, responsibility, honesty, respect, simplicity, tolerance, unity, open-mindedness, love, happiness, freedom, empathy, humility. Cooperative learning is one of the appropriate strategies to teach those skills and values. When it is applied properly, many living values will be  studied by  students, those are: cooperation, responsibility, tolerance, unity, respect, caring, love.   Key Words: social and democratic  society, Social skills, living values, cooperative learning